The Influence of Work Conflict and Work Stress on Employee Performance at PT. Panin Dai-Ichi Life - Hamsinah Hamsinah (PINISI Discretion Review, 2019)
The high demand for performance or performance target standards determined by the company, makes employees will try and be motivated to achieve the performance targets set by the company. Sometimes in the process, it creates a separate conflict for employees. The type of research conducted in this research is associative research where this research has the highest level compared to descriptive and comparative research because this research can be theory which also works to explain, predict, and control a symptom that occurs. The result is known that Fcount 5.546 > Ftable 3.904 or Sig value 0.000 <0.05, then Ho is rejected and Ha is accepted, so it can be concluded that work conflict (X1) and work stress (X2) have a simultaneous effect on job satisfaction (Y). Meanwhile, the contribution of Work Conflict (X1) and Job Stress (X2) to Job Satisfaction (Y) is 5.7% and the remaining 94.3% is influenced by other factors.